2018
DOI: 10.1186/s12933-018-0699-7
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic treatment patterns and specialty care utilization among patients with type 2 diabetes and cardiovascular disease

Abstract: BackgroundTo evaluate real-world patient characteristics, medication use, and health care utilization patterns in patients with type 2 diabetes with established cardiovascular disease (CVD).MethodsCross-sectional analysis of patients with type 2 diabetes seen at Cleveland Clinic from 2005 to 2016, divided into two cohorts: with-CVD and without-CVD. Patient demographics and antidiabetic medications were recorded in December 2016; department encounters included all visits from 1/1/2016 to 12/31/2016. Comorbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 21 publications
5
44
0
1
Order By: Relevance
“…In the total Cleveland Clinic study population, usage of GLP‐1RAs and SGLT2is was each <5.5%, and even lower in the ASCVD group. The majority of patients (>80%) had not had an endocrinology visit in the past year …”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In the total Cleveland Clinic study population, usage of GLP‐1RAs and SGLT2is was each <5.5%, and even lower in the ASCVD group. The majority of patients (>80%) had not had an endocrinology visit in the past year …”
Section: Discussionmentioning
confidence: 76%
“…Findings from the current analysis are consistent with those of a recent similar cross‐sectional analysis based on electronic health record data from Cleveland Clinic (Ohio and Florida) for the year 2016 . The Cleveland Clinic study included data from 96 569 individuals with T2DM and reported that 42.8% had CVD, which is highly consistent with the proportion with established ASCVD in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the performance of our CP for identification of incident T2DM was very poor. As noted in prior research, identification of patients with T2DM within large health care systems does not always indicate that such systems are the primary or initial site of diabetes management . As outlined in a recent study, requiring at least one encounter coded as primary care or endocrinological/diabetes in each of the prior 2 years might better differentiate incident or new onset T2DM from patients with prevalent T2DM .…”
Section: Discussionmentioning
confidence: 95%